Peran Harga, Fasilitas Dan Pelayanan Terhadap Kepuasan Konsumen Hotel Lotus Garden & Resort Kediri - Hery Purnomo (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The purpose of the study was to determine the significance of prices, facilities, and services partially and simultaneously to consumer satisfaction of Lotus Garden & Resort Kediri Hotel service users, after the Covid-19 pandemic. Consumer satisfaction indicators used are the provision of good service, speed of work, responsiveness, employees can diagnose quickly, and employees pay attention to consumer complaints. The research strategy is descriptive quantitative. Survey methodology was used in this study. All people who have used the services of Lotus Garden & Resort Hotels are a sample population. Forty individuals were selected by stratified random selection and a snowball sampling process. Multiple linear regression analysis is performed to analyze the data. Overall client satisfaction with hotel services was found to be 85 percent due to price, amenities, and service.